Causes of the word meaninsg change (On middle aged Turkic written manuscripts) (Eurasian Journal of Philology Science and Education, 2016)
There were ambigiuos words at the same time with unique words in old Turkic written manuscripts. Linguists consider extension of semantic field of the word and having more than one meaning as polysemy. Changing and development can occur to meaning of the word in language lexis.People became to know things and facts and their features and secrets of the surrounding world by the development of the society. Things which are recognized newly do not always cause appearance of new words. They are called by the names which had existed in word stock before, they take additional meaning to previous ones. The article considers the expansion and distribution of meanings of the nouns in literary monuments language in XI-XII centuries.
Keywords: meaning of the word; extension of the meaning; narrowing of the meaning; historical monuments; outer factor; inner factor.